The Comparison of Two Types of Treatment (High Dose and Low Dose IVIG) in Children with GBS in Mofid Hospital - Parvaneh Karim-Zadeh; Mohammad Ghofrani (University of Social Welfare and Rehabilitation Sciences, 2003)
Objective: Acute inflammatory demyelinating peripheral neuropathy (Guillain-Barre-Syndrome) is by far the most common cause of immune-mediated peripheral nerve disease in children and with the near disappearance of poliomyelitis, is responsible for the great majority of cases of acute flaccid paralysis. Several controlled studies have done with corticosteroids, plasma pheresis and IVIG in pediatric patients. IVIG treatment can be done in two types of treatment: 1- High dose that means 1gr/kg/day for 2 days. 2- Low dose that means 400mg/kg/day for 5 days. Several studies in other countries have shown faster rate of recovery in patients who received total dose of IVIG in 2 days as opposed to 5 days. Materials & Methods: Because we have not any study about this two types of treatment in IRAN we decided to comparison this two types of IVIG treatment. So the patients that referred to Mofid children hospital for weakness and we diagnosed GBS (with history, physical examination, laboratories and EMG-NCV) are divided in two groups: 1- High dose IVIG treatment (experimental group). 2- Low dose IVIG treatment (control group) Then the results evaluated. Results: Our findings included that in high dose IVIG therapy we have faster rate of recovery and the Hospital stay is shorter than low dose IVIG-therapy. Also in this type of treatment "because the patients cure faster" , so complications are decreased in them. In the group of high dose IVIG therapy, lower and upper extremities weakness decreased in time. Conclusion: We did not receive any relationship between side effects of drugs and the type of treatment. The relationship between high dose IVIG therapy and drug side effects was not significant.